Find the roots of the quadratic equation \[{\text{3}}{{\text{x}}^2}{\text{ - 4}}\sqrt 3 {\text{x + 4 = 0}}\]
Answer
Verified
483k+ views
Hint: We will use formula of Sridhar acharya here. Which is given as, if, a quadratic equation, \[{\text{a}}{{\text{x}}^2}{\text{ + bx + c = 0}}\] then, the roots of the equations would be, \[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\]
Complete step by step answer:
Here, the given equation for us is, \[{\text{3}}{{\text{x}}^2}{\text{ - 4}}\sqrt 3 {\text{x + 4 = 0}}\].
The above equation is in the form of \[{\text{a}}{{\text{x}}^2}{\text{ + bx + c = 0}}\]
$\Rightarrow$ \[a = 3,b = - 4\sqrt 3 ,c = 4\]
So, now if we use the formula of Sridhar acharya, we will get,
\[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\]
On substituting values of a, b and c, we get,
\[ \Rightarrow x = \dfrac{{ - ( - 4\sqrt 3 ) \pm \sqrt {{{( - 4\sqrt 3 )}^2} - 4.3.4} }}{{2.3}}\]
\[ \Rightarrow x = \dfrac{{4\sqrt 3 \pm \sqrt {16 \times 3 - 48} }}{6}\]
\[ \Rightarrow x = \dfrac{{4\sqrt 3 \pm \sqrt {48 - 48} }}{6}\]
\[ \Rightarrow x = \dfrac{{4\sqrt 3 }}{6}\]
\[ \Rightarrow x = \dfrac{{2\sqrt 3 }}{3}\]
\[ \Rightarrow x = \dfrac{2}{{\sqrt 3 }}\]
So, we have the solution of the equation, \[{\text{3}}{{\text{x}}^2}{\text{ - 4}}\sqrt 3 {\text{x + 4 = 0}}\] as \[x = \dfrac{2}{{\sqrt 3 }}\].
Note: Here in this equation, we get our discriminant, \[\sqrt {{b^2} - 4ac} \]\[ = 0\] which means this quadratic equation will have a equal root. That means the two roots of the equation will be equal and of the same sign. We can also approach this problem in a different way. We can write this equation as \[{(\sqrt 3 x - 2)^2}\]and proceed with the problem to find, \[x = \dfrac{2}{{\sqrt 3 }}\].
Complete step by step answer:
Here, the given equation for us is, \[{\text{3}}{{\text{x}}^2}{\text{ - 4}}\sqrt 3 {\text{x + 4 = 0}}\].
The above equation is in the form of \[{\text{a}}{{\text{x}}^2}{\text{ + bx + c = 0}}\]
$\Rightarrow$ \[a = 3,b = - 4\sqrt 3 ,c = 4\]
So, now if we use the formula of Sridhar acharya, we will get,
\[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\]
On substituting values of a, b and c, we get,
\[ \Rightarrow x = \dfrac{{ - ( - 4\sqrt 3 ) \pm \sqrt {{{( - 4\sqrt 3 )}^2} - 4.3.4} }}{{2.3}}\]
\[ \Rightarrow x = \dfrac{{4\sqrt 3 \pm \sqrt {16 \times 3 - 48} }}{6}\]
\[ \Rightarrow x = \dfrac{{4\sqrt 3 \pm \sqrt {48 - 48} }}{6}\]
\[ \Rightarrow x = \dfrac{{4\sqrt 3 }}{6}\]
\[ \Rightarrow x = \dfrac{{2\sqrt 3 }}{3}\]
\[ \Rightarrow x = \dfrac{2}{{\sqrt 3 }}\]
So, we have the solution of the equation, \[{\text{3}}{{\text{x}}^2}{\text{ - 4}}\sqrt 3 {\text{x + 4 = 0}}\] as \[x = \dfrac{2}{{\sqrt 3 }}\].
Note: Here in this equation, we get our discriminant, \[\sqrt {{b^2} - 4ac} \]\[ = 0\] which means this quadratic equation will have a equal root. That means the two roots of the equation will be equal and of the same sign. We can also approach this problem in a different way. We can write this equation as \[{(\sqrt 3 x - 2)^2}\]and proceed with the problem to find, \[x = \dfrac{2}{{\sqrt 3 }}\].
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE